The Influence of Service Quality on Customer Satisfaction of Regional Drinking Water Company (PDAM) “Delta Tirta” - Iva Mareta Dewi; Lailul Mursyidah (Indonesian Journal of Public Policy Review, 2022)
Good public services are services that can meet Servqual indicators, that’s tangible, reliability, responsiveness, assurance, and empathy. However, there are still many services that are not good. The problems that occur in PDAM "Delta Tirta" Sidoarjo Regency are still complaining about the quality of the water being cloudy, sandy, water turning off at certain hours and increasing the increasingly expensive tariffs that are not in accordance with the service, thus causing dissatisfaction by customers. This study aims to examine the effect of service quality on customer satisfaction at PDAM "Delta Tirta" Sidoarjo Regency either simultaneously or partially. This research method uses correlational quantitative. The focus of the research is the quality of service and customer satisfaction and the customers of PDAM "Delta Tirta" Sidoarjo Regency as research subjects. The sample is 400 respondents. Data derived from questionnaires were then analyzed using multiple linear regression analysis and classical assumption test. The results show that 1) the quality of service has a positive influence on customer satisfaction of PDAM "Delta Tirta" Sidoarjo Regency, 2) service quality has a significant influence on customer satisfaction of PDAM "Delta Tirta" Sidoarjo Regency, and 3) service quality has a positive and significant impact on customer satisfaction of PDAM "Delta Tirta" Sidoarjo Regency.